Analysis of the Confidence Level of Male Futsal Players Aged 16-18 Years From the Gadjah Agung Sumedang Team - Muhammad Iqbal Sholihin; Yudha Munajat Saputra; Dewi Susilawati (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research aims to find out how much self-confidence has increased in male futsal players aged 16-18 years from the Gadjah Agung Sumedang Team. In this club, many futsal players lack confidence before the match. Self-confidence is a positive thing and influences a match. As a result, the match will become monotonous if the player has good performance but lacks mental confidence. This research uses a quantitative descriptive method which is an explanation, describing conditions and situations. This type of research uses the survey method. A survey is a research that attempts to collect data on one or several variables taken from members of the population in the research. Research design is all the processes required for planning and implementing research. The results of this research are in the form of a percentage analysis of the level of self-confidence in the high category of 66.66% (20 athletes) and the very high category of 33.33% (10 athletes) with an internal high category of 70% (21 athletes) and the very high category. 30% (9 athletes) and external factors in the medium category 3.33% (1 athlete), while for the high category, it was 70% (21 athletes), and in the very high category 26.66% (8 athletes). In the role of internal factors in achieving achievement, there are indicators of self-concept, self-esteem, and physical condition. Where the three of them show that self-confidence in internal factors is in the high category for male athletes. The role of external factors, which also contain three indicators, namely education, work, and environment, male athletes' level of confidence is in the high category. It is known from the analysis that the level of self-confidence of male futsal player Gadjah Agung Sumedang aged 16-18 years is not low.